The long road from urban experimentation to the transformation of urban planning practice: The case of tactical urbanism in the city of Barcelona - Franziska Schreiber (Journal of Urban Mobility)
Managing the transition to sustainable urban mobility requires significant changes in planning and decision-making approaches. Urban (street) experiments, particularly Tactical Urbanism (TU), have emerged as promising tools for catalyzing these changes. However, despite their growing popularity, empirical studies of their long-term impacts are scarce. This paper examines the potential of TU to drive innovation in municipal planning practice, and the conditions that enable or hinder this. The study uses a longitudinal case study analysis with a mixed methods approach to reconstruct the use of TU and its impact on planning in Barcelona, Spain, between 2013 and 2023. The results show that while TU has brought about innovations and promoted changes in planning by fostering new ways of thinking, doing, and organizing among municipal planners, its impact on planning practices remains limited. The study suggests that political pressure on planners to avoid failure, bureaucratic hurdles, and the lack of (process) learning are among the main barriers to generating valuable lessons for planning and institutionalizing innovations. At the same time, the study highlights the critical role of avant-garde planners, the involvement of intermediaries, and the alignment between TU and the municipal agenda to increase the impact of TU. The research reveals important insights for planning practitioners and policy makers seeking to promote sustainable mobility transitions through TU. It also identifies directions for future research to further deepen the understanding of the complex dynamics that shape the innovation potential of TU for planning.